Writing Centres as the Driving Force of Programme Development: From Add-on Writing Courses to Content and Literacy Integrated Teaching - Göpferich, Susanne E. (Journal of Academic Writing, 2016)
Academic writing courses and subject-matter courses have been taught independently to a large extent at many European universities following a ‘study skills model’ (Lea and Street 1998). An integrated approach, however, both in students’ L1 (or their language of instruction) and in English (if this is not their L1), in accordance with Lea and Street’s ‘academic literacies model’ has a number of advantages. Introducing an academic literacies model, however, is difficult to implement since it requires the joint effort of both subject-domain teachers and language teachers and involves deviating from familiar teaching methods. To implement the changes required, a three-level approach has been developed at Justus Liebig University (JLU), Giessen/Germany, as one of several measures in a university-wide project. In this approach, the university’s writing centre and teaching centre take over the role of ‘motors’ of literacy development in all disciplines. The macro-level of this three-level approach encompasses central services provided by these centres as well as university-wide literacy development policies. The meso-level addresses programme development, and the micro-level, curriculum and syllabus adaptations for individual courses. The article provides insight into the measures to be taken at each of these levels based on a review of prior research on Integrating Content and Language in Higher Education (ICLHE) (Gustafsson 2011, Gustafsson and Jacobs 2013 and Wilkinson and Walsh 2015) and the central role that writing centres and teaching centres can play in this process.